MODEL PEMBELAJARAN CLASSROOM MEETING DALAM PENDIDIKAN AGAMA ISLAM: Pembelajaran Classroom Meeting - Suwartiningsih (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2020)
Teaching and learning activities are a process in order to achieve learning objectives. Teaching is the teacher's effort to create conditions or regulate the environment in such a way that there is interaction between students, teachers and their environment. In the teaching and learning process, a teacher is never the same in delivering the subject matter. In the teaching and learning process, the class meeting model is a very important foundation to be applied so that students can understand the lessons being taught. The teaching and learning process like this causes students to be more motivated to learn more actively in class and will get better learning outcomes. We often encounter this when the teacher is explaining lessons, especially Islamic Education.